(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
In a market economy in Russia, every organization and individual business entity needs competent financial planning. Financial planning allows you to determine the current objectives of an enterprise to achieve maximum financial results, as well as identify unused hidden reserves and unfavorable factors that negatively affect the financial and economic activities of the organization. The key to the success of an enterprise is the formation of a financial plan for the current and future reporting periods and the development of strategies for its implementation.